2010
DOI: 10.1111/j.1469-8986.2010.00989.x
|View full text |Cite
|
Sign up to set email alerts
|

Event-related brain potential correlates of identity negative priming from overlapping pictures

Abstract: Event-related potentials (ERPs) were obtained from an identity priming task, where a green target had to be selected against a superimposed red distractor. Several priming conditions were realized in a mix of control (CO), negative priming (NP), and positive priming (PP) trials. PP and NP effects in reaction times (RTs) were significant. ERP results conceptually replicate earlier findings of left-posterior P300 reduction in PP and NP trials compared to CO. This ERP effect may reflect the detection of prime-pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 37 publications
3
25
0
Order By: Relevance
“…Therefore, May et al stated that a larger basis of data is necessary in order to answer the question at which level of processing NP is produced [25]. In a recent ERP study we found comparable processing of distractor-target and target repetition trials in the early stages of a trial and diverging processing at later stages associated with activation of higher brain regions [47]. This pattern supports the following propositions: First, object repetition may lead to a faster perceptual processing for both NP and PP conditions; second, a delaying, negative priming effect occurs after the full categorization of the stimuli, which is in contrast to predictions derived from distractor inhibition theory.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Therefore, May et al stated that a larger basis of data is necessary in order to answer the question at which level of processing NP is produced [25]. In a recent ERP study we found comparable processing of distractor-target and target repetition trials in the early stages of a trial and diverging processing at later stages associated with activation of higher brain regions [47]. This pattern supports the following propositions: First, object repetition may lead to a faster perceptual processing for both NP and PP conditions; second, a delaying, negative priming effect occurs after the full categorization of the stimuli, which is in contrast to predictions derived from distractor inhibition theory.…”
Section: Introductionmentioning
confidence: 77%
“…[22], [47]: While TT trials usually cause a strong acceleration (PP), the acceleration is weaker in DD trials. DT and TD trials show a deceleration (NP) which is often weaker for TD trials.…”
Section: Methodsmentioning
confidence: 99%
“…This significant effect only occurred when participants also displayed the behavioral correlates of NP and was therefore functionally linked to NP (Groh-Bordin & Frings, 2009). Further, in a task of superimposed and colored pictures, the left-posterior P300 amplitude and frontal late positive complex (LPC) amplitude were reduced in IR trials and in AR trials alike (Behrendt et al, 2010); the same result was obtained in a Flanker NP task (Gibbons, 2009;Stahl & Gibbons, 2007). The underlying processes were discussed as reflecting processes related to perceived prime-probe-similarity (Behrendt et al, 2010).…”
Section: What Are the Neural And Electrophysiological Correlates Of Np?mentioning
confidence: 93%
“…Further, in a task of superimposed and colored pictures, the left-posterior P300 amplitude and frontal late positive complex (LPC) amplitude were reduced in IR trials and in AR trials alike (Behrendt et al, 2010); the same result was obtained in a Flanker NP task (Gibbons, 2009;Stahl & Gibbons, 2007). The underlying processes were discussed as reflecting processes related to perceived prime-probe-similarity (Behrendt et al, 2010). Gibbons (2009) noticed a specific effect of NP on the N400 and Gibbons and Frings (2010) found an IR specific late P3 complex in a NP task with spatial uncertainty.…”
Section: What Are the Neural And Electrophysiological Correlates Of Np?mentioning
confidence: 99%
“…Negative priming describes the phenomenon of a prolonged reaction time (RT) and/or a greater number of errors when the participants have to respond to a target that was ignored in the preceding trial [32, 33]. In this task, the participants were required to process pairs of trials that were structured according to a prime-probe schema.…”
Section: Methodsmentioning
confidence: 99%